Experiences of women seeking care for abortion complications in health facilities: Secondary analysis of the WHO Multi‐Country Survey on Abortion in 11 African countries. (5th December 2021) - Govule, Philip; Baumann, Sasha; Dossou, Jean‐Paul; Calvert, Clara; Goufodji, Sourou; Mehrtash, Hedieh; Tuncalp, Özge; Adu‐Bonsaffoh, Kwame; Compaoré, Rachidatou; Filippi, Véronique
Abstract: Objective: Despite evidence of acute and long‐term consequences of suboptimal experiences of care, standardized measurements across countries remain limited, particularly for postabortion care. We aimed to determine the proportion of women reporting negative experiences of care for abortion complications, identify risk factors, and assess the potential association with complication severity. Methods: Data were sourced from the WHO Multi‐Country Survey on Abortion for women who received facility‐based care for abortion complications in 11 African countries. We measured women's experiences of care with eight questions from an audio computer‐assisted self‐interview related to respect, communication, and support. Multivariable generalized estimating equations were used for analysis. Results: There were 2918 women in the study sample and 1821 (62%) reported at least one negative experience of postabortion care. Participants who were aged under 30 years, single, of low socioeconomic status, and economically dependent had higher odds of negative experiences. Living in West or Central Africa, rather than East Africa, was also associated with reportedly worse care. The influence of complication severity on experience of care appeared significant, such that women with moderate and severe complications had 12% and 40% higher odds of reporting negative experiences, respectively. Conclusion: There were widespread reports of negative experiences of care among women receiving treatment for abortion complications in health facilities. Our findings contribute to the scant understanding of the risk factors for negative experiences of postabortion care and highlight the need to address harmful provider biases and behaviors, alleviate health system constraints, and empower women in demanding better care. Synopsis: Women seeking treatment for abortion‐related complications in health facilities reported widespread negative experiences of care in 11 African countries.